The Influence of Transformational Leadership and Work Motivation on Employee Performance Mediated by Job Satisfaction (In the East Nusa Tenggara High Prosecutor's Office) - Prakoso, Ario Wirawan (Jurnal Multidisiplin Indonesia, 2023)
This study aims to determine the influence of transformational leadership, work motivation on employee performance mediated by Job Satisfaction (Empirical Study on the High Court of East Nusa Tenggara). The job satisfaction variable here functions as a mediating variable which researchers want to prove that it has an impact on employee performance. The company that was sampled in this study was the east nusa Tenggara high prosecutor's office. Mining work is a type of heavy work that requires work involvement from employees in order to achieve company goals, therefore a supervisor is needed who is able to move or direct employees to be involved in their work, besides that with a motivating language it is hoped that employees will be more involved in their work. This research was conducted on 230 employees working at the east nusa Tenggara high prosecutor's office, belu district prosecutor's office, west sumba district prosecutor's office, kupang city district prosecutor's office, kupang district prosecutor's office and sikka district attorney's office. where the results obtained transformational leadership and work motivation have a significant effect on job satisfaction. However, it does not have a direct effect on employee performance. Therefore, the east nusa Tenggara high prosecutor's office needs to maintain regular internal training within the organization and must increase the provision of rewards and punishments to employees who work very well.